(untitled) (Third Sector Social Economic Review, 2026)
Understanding the factors that lead employees to remain silent in the workplace is essential. While employee silence has been extensively studied in correlational research, studies exploring the impact of leadership styles and emerging organizational attitudes on silence are still limited. This study investigates the direct and indirect relationships among toxic leadership, organizational indifference, and employee silence. The study was conducted in April 2024 with quantitative method and correlational survey type. Data were collected from 351 administrative staff of a state university in the Central Black Sea Region of Türkiye. According to the findings of bootstrap regression analysis, toxic leadership contributes in positive direction to the explanation of organizational indifference and employee silence. However, organizational indifference contributes in the positive direction to the employee silence. Finally, toxic leadership contributes in the positive direction to the employee silence through organizational indifference. This mediation effect, which was identified for the first time, is the most important finding of the study in terms of its contribution to the literature. It is essential to recognize that the toxic behaviors exhibited by managers not only affect individual relationships but also foster an atmosphere of indifference throughout the organization, pushing employees into silence. Therefore, managers should adopt leadership styles that prioritize constructive communication and employees should be encouraged to express their thoughts through appropriate channels.